Pengaruh Pengalaman Kerja Terhadap Produktivitas Pengrajin Untuk Menunjang Pendapatan Pengrajin Ukiran Kayu - Sri Muliani, Ni Made; Suresmiathi, A. A. Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 5, Mei 2016 (pp. 530-651), 2016)
Gianyar was one of regency in Bali while still did the wooden hadycrafts industry for made the souvenirs while tourist like. For survive the wooden handycrafts industry, management look for teeneger while has work experience and technology for impact the worker revenue. The worker while has good work experience and support by technology can be increasing productivity and increasing the worker revenue. The result of quisioner about the impact of work experience and technology for worker productivity to the income of revenue. From the quisioner, will get the quality information to the income revenue and used skorsing for get the quantity data. The result has showed work experience was impact positif and signifivanto productivity while ? was 0,621. Technology was impact positif and significant to productivity while ? was 0,557. Work experience was positif and significant to encome of revenue while ?was 0,715.But work experience was not impact to income of revenue while ? was -0,451.And work experience was impact positif and significant to income of revenue while ? was 0,477.
Keywords: work experience, technology, productivity and revenue